A systematic review about the possibility of transmission of the SARS-CoV-2 antibody during breastfeeding (Research, Society and Development, 2023)
Breastfeeding by COVID-19 positive mothers still deserves attention and care regarding the consequences for the baby. To date, studies demonstrate no risk. In view of this, there is a need to perform a systematic review and collect studies that have shown the presence of SARS-CoV-2 in human milk, by measuring IgM, IgG and IgA in biological material. After searching PubMed, Web of Science, Scopus, Google Scholar databases, 147 studies were identified, of which 37 at some point addressed breastfeeding and COVID-19, and 14 of which addressed antibody dosages in breast milk. Of these, one used the ELISA test for IgA detection. In the other studies, the methodology used was RT-PCR to detect the SARS-CoV-2 virus in breast milk, where the presence of the virus was detected in a few samples. These studies confirmed that SARS-CoV-2 can be identified in breast milk, but could not elucidate about the validation of the method and its sensitivity. In addition, there was no description if the viral load present in the milk would be sufficient to infect the baby. Furthermore, no completed research involving serological tests for the detection of antibodies in human colostrum has been found. Thus, more serological studies on COVID-19 positive breastfeeding mothers are mandatory.